Immune-metabolic balance in stressed rats during Candida albicans infection - Rodriguez Galan, Maria Cecilia (2010)
We evaluated the host metabolic response to chronic varied stress during infection with the fungus Candida albicans. We used four groups of female Wistar rats: normal uninfected and unstressed, stressed, C. albicans infected and infected, and stressed. Infected rats reacted with rapid metabolic adjustments, evident as anorexia and body weight loss, partly mediated by glucocorticoids and TNF-á. Higher circulating levels of IL-6 and glucose (p < 0.05) revealed the progress and catabolic effect of the inflammatory response. Infected and stressed rats instead showed anorexia associated with infection and weight loss as the result of reduced food intake. This group exhibited a prompt reduction in circulating leptin on day 3 (p < 0.05), reduction in glucose levels and depletion of hepatic glycogen depots. We also evaluated the contribution of TNF-á, glucocorticoids, and food deprivation to liver damage. Lipid peroxidation in liver detected in the infected and infected-stressed groups was exacerbated by the glucocorticoid receptor antagonist RU 486, suggesting the modulatory activity of glucocorticoids, while hepatic fat accumulation and glycogen depletion decreased with anti-TNF-á treatment. Food deprivation exacerbated liver injury while the response to stress contributed to greater fungal colonization. Our findings emphasize the impact of metabolic alterations on tissue damage when the host immune activity is modulated by stress mediators.